Infection of sardine eggs by a parasitic dinoflagellate Ichthyodinium chabelardi hollande and cachon, 1952 in croatian waters - Dulčić, Jakov (Annales. Series historia naturalis, 1998)
The infection of sardine eggs by a parasitic dinoflagellate (Ichthyodinium chabelardi) in the eastern central Adriatic was investigated. This syndinian parasitizes the vitelline vesicle of sardine embryos and after eclosion burststhe yolk causing the death of the newly hatched larvae. Sardine eggs aremainly infected during winter period...
Keywords: Adriatic Sea; ikre; Jadransko morje; sardele; zajedalci